Karyological studies on the annual members of the genus Carduus L. (Asteraceae, Cardueae) from Turkey - Gedik, Osman; Kiran, Yasar; Arabaci, Turan; Kostekci, Serkan (Firenze Univ Press, 2014)
The somatic chromosome numbers and detailed morphometric properties of eight of the nine annual Turkish Carduus L. taxa were examined. The somatic chromosome numbers were 2n = 2x = 22 in C. rechingerianus Kazmi; 2n = 2x = 28 in C. argentatus L., C. acicularis Bertol. and C. pycnocephalus L. subsp. albidus (M. Bieb.) Kazmi; 2n = 2x = 34 in C. pycnocephalus subsp. arabicus (Jacq. ex Murray) Nyman and subsp. breviphyllarius P. H. Davis; 2n = 2x = 50 in C. nervosus K. Koch.; and 2n = 2x = 62 in C. pycnocephalus subsp. pycnocephalus. Karyotype analysis indicated that chromosomes of the Carduus taxa generally have centromere median region (m), submedian region (sm), and rarely median point (M) of the chromosome. A pair of satellite chromosomes (sat-chromosome) was observed in C. pycnocephalus subsp. breviphyllarius. The findings for each of the analysed taxa are compared with the results of previous studies. The chromosome number and morphology of C. nervosus, C. rechingerianus, C. argentatus, C. pycnocephalus subsp. arabicus and subsp. breviphyllarius are newly reported here.
Keywords: chromosome number; Carduus; karyotypes; Turkey